2010
DOI: 10.1007/s10535-010-0133-9
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide alleviated chromium toxicity in wheat

Abstract: Effects of H 2 S on seed germination under chromium (Cr) stress were investigated in wheat (Triticum aestivum L.). Under Cr stress, the percentage of germination of wheat seeds decreased, but this decrease could be alleviated by pretreatment with NaHS, an H 2 S donor, in a dose-dependent manner. Furthermore, NaHS significantly enhanced the activities of amylase, esterase, superoxide dismutase, catalase, ascorbate peroxidase, and guaiacol peroxidase in Cr-stressed germinating seeds, whereas reduced the Cr-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(73 citation statements)
references
References 32 publications
(28 reference statements)
5
65
1
Order By: Relevance
“…In present study, pretreatment with NaHS enhanced survival percentage of 2.5-dayold maize seedlings in a concentration-dependent manner (Fig. 1), consistent with the results of Zhang et al (2009bZhang et al ( , 2010a in wheat and sweetpotato under Cr and osmotic stress. All of above-mentioned studies indicated that H 2 S may be relative to the acquisition of stress tolerance including heat tolerance in plants, but their mechanisms are not fully clear.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In present study, pretreatment with NaHS enhanced survival percentage of 2.5-dayold maize seedlings in a concentration-dependent manner (Fig. 1), consistent with the results of Zhang et al (2009bZhang et al ( , 2010a in wheat and sweetpotato under Cr and osmotic stress. All of above-mentioned studies indicated that H 2 S may be relative to the acquisition of stress tolerance including heat tolerance in plants, but their mechanisms are not fully clear.…”
Section: Discussionsupporting
confidence: 91%
“…In cucumber seedlings, total and isozymatic activities and corresponding transcripts of SOD, CAT, GPX and APX were activated differentially by NaHS, thus resulting in the alleviation of oxidative damage induced by boron (Wang et al 2010. Pretreatment with exogenous NaHS enhanced the activities of SOD, CAT, APX and GPX in wheat (Triticum aestivum L.) seedlings, reduced the Cr-induced increase in over-production of MDA and H 2 O 2 , followed by alleviated decrease in the germination rate of wheat seeds under Cr stress in a dose-dependent manner (Zhang et al 2010a). Again, application of NaHS increased the activities of APX, GR, dehydroascorbate reductase (DHAR) and γ-glutamylcysteine synthetase (γ-GCS), a key enzyme of GSH biosynthesis, as well as the contents of AsA, GSH, total ascorbate and total glutathione under water stress, which in turn decreased the MDA accumulation induced by water deficiency in wheat compared to control without NaHS treatment (Shan et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is therefore the third discovered gaseous signaling molecule, following the discoveries of Nitric oxide (NO) and Carbon monoxide (CO). In plants, H 2 S is mainly produced via the L-/D-cysteine desulfhydrase enzymes (LCD/ DCD) and it has been reported to be involved in stress responses to drought, heat, heavy metal and salt during seed germination and seedling growth (ZHANG et al, 2010a;JIN et al, 2011;LAI et al, 2014;LI et al, 2014). Applications of H 2 S could also significantly improve root morphology, chlorophyll content and photosynthetic activity under Pb stress (ALI et al, 2014).…”
Section: Introductionmentioning
confidence: 99%